Using the Yeast Three-Hybrid System to Identify Proteins that Interact with a Phloem-Mobile mRNA - Cho, Sung Ki; Kang, Il-Ho; Carr, Tyrell; Hannapel, David J. (Frontiers in Plant Science, 2012)
Heterografting and RNA transport experiments have demonstrated the long-distance mobility of StBEL5 RNA, its role in controlling tuber formation, and the function of the 503-nt 3´ untranslated region (UTR) of the RNA in mediating transport. Because the 3´ UTR of StBEL5 is a key element in regulating several aspects of RNA metabolism, a potato leaf cDNA library was screened using the 3´ UTR of StBEL5 as bait in the yeast three-hybrid system to identify putative partner RNA-binding proteins (RBPs). From this screen, 116 positive cDNA clones were isolated based on nutrient selection, HIS3 activation, and lacZ induction and were sequenced and classified. Thirty-five proteins that function in either RNA- or DNA-binding were selected from this pool. Seven were monitored for their expression profiles and further evaluated for their capacity to bind to the 3´ UTR of StBEL5 using β-galactosidase assays in the yeast three-hybrid system and RNA gel-shift assays. Among the final selections were two RNA-binding proteins, a zinc-finger protein, and one protein, StLSH10, from a family involved in light signaling. In this study, the yeast three-hybrid system is presented as a valuable tool to screen and verify interactions between target RNAs and putative RNA-binding proteins. These results can shed light on the dynamics and composition of plant RNA-protein complexes that function to regulate RNA metabolism.